2003
DOI: 10.1046/j.1360-0443.2003.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

A flicker paradigm for inducing change blindness reveals alcohol and cannabis information processing biases in social users

Abstract: Alcohol and cannabis processing biases are found at levels of social use, have the potential to influence future consumption and for this reason merit further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
113
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 27 publications
11
113
0
1
Order By: Relevance
“…In this framework where alcohol has acquired strong motivational properties, alcohol-related stimuli may be seen as 'hijacking' the attention of heavy drinkers and alcoholics (e.g., Johnsen et al 1994;Townshend and Duka 2001;Waters and Green 2003;Noël et al 2005Noël et al , 2006Jones et al 2003). For instance, when performing the alcohol Stroop task, sober alcoholics are slower than non-alcoholic controls in naming the color of alcohol-related words (e.g., Johnsen et al 1994;Stetter et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In this framework where alcohol has acquired strong motivational properties, alcohol-related stimuli may be seen as 'hijacking' the attention of heavy drinkers and alcoholics (e.g., Johnsen et al 1994;Townshend and Duka 2001;Waters and Green 2003;Noël et al 2005Noël et al , 2006Jones et al 2003). For instance, when performing the alcohol Stroop task, sober alcoholics are slower than non-alcoholic controls in naming the color of alcohol-related words (e.g., Johnsen et al 1994;Stetter et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al (2003) proposed that for alcohol users attention to alcohol-related stimuli is augmented. As a result, the more people drink the more likely it is that alcohol-related stimuli capture their attention automatically, resulting in the AMB presently observed.…”
Section: Discussionmentioning
confidence: 99%
“…Cycling presentations continued until the participant spotted "the change" (it was implied that there was only one change) and it was found that those who spotted the alcohol-related change had higher consumptions than those who spotted the neutral change. In a subsequent flicker paradigm experiment Jones et al (2003) showed that when only one change was given to be detected, heavier social drinkers spotted the change quicker when it was alcohol-related than did a lighter social drinking control group and this was not the case with the neutral change. This was replicated with problem drinkers in treatment and using slightly modified stimuli by Jones et al (2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations